Peningkatan Kerjasama Tim Menggunakan Metode Outbound - Eva Mirza Safitri; Netty Lisdiantini; Aminudin Azis (P3I Politeknik Negeri Madiun, 2021)
Business administration simulation course where students do role playing in groups consisting of 3-4 students who have different roles. The roles range from manager, secretary, finance and marketing. At the beginning of this course, students make a selection to compete for the position of company secretary and manager position. After selecting one company secretary who will later lead the simulation, 7 managers were also selected. of these seven managers must create a company that is mutually integrated both in the field of services and trade. Based on these data, it can be concluded that the problems faced by the class are related to teamwork, therefore, an appropriate method is needed to handle them so that the simulation process can run well and get the expected results. without teamwork and good relations within the group it is impossible to achieve this goal because all the work and assignments in this course require the roles of group members. The method offered in this study is the outbound learning method. Outbound is an open nature-based learning method in creative and attractive ways, so that learning becomes a comfortable and very enjoyable activity. The purpose of this outbound is to practice recognition and build confidence in learning, communicating with other individuals and teamwork. The results of this study indicate that there is a significant increase in each indicator of student teamwork between before and after outbound learning is applied.